Students' perceptions on the effectiveness of Islamic and Asian Civilization Mooc as a blended learning course - Ab. Halim, Adlina; Othman, Normala; Ab. Majid, Arfah; Mohd Yusof, Ahmad Nasir; Azri, Norasyikin (Human Resource Management Academic Research Society, 2021)
Blended learning is an integration of face-to-face, online teaching and learning process whereby it has been developed to improve the conventional learning method. Massive Open Online Courses (MOOCs) platform in Malaysia has been designed purposely to incorporate the blended learning approaches. Therefore, this study aims to examine students' perceptions on the effectiveness of Islamic and Asian Civilization MOOC as a blended learning course. The study employed a quantitative approach through survey method and purposive sampling was chosen as the sampling technique. The study was conducted among first year students in 19 Malaysian public universities by using an online questionnaire. A total number of 1373 public university students from five different zones were involved as respondents. The results revealed that the respondents have good perception on the effectiveness of MOOC platform with a mean score of 4.07. In addition, the finding also shows a significant relationship between student's perceptions on the effectiveness and their acceptance of MOOCs. The students' perspective also delineates that blended learning courses will positively impact the students' knowledge, motivation and soft skill. This study highlights the importance of the students’ viewpoints in determining the effectiveness of a blended learning approach such as MOOCs.